Refined estimates of the depths of magma chambers beneath the Reykjanes and Kolbeinsey Ridges, and implications for the structure of oceanic crust - Scott, Jameson Lee (The Ohio State University, 2009)
The mid-Atlantic ridge is the divergent plate boundary between North and South America to the west and Europe and Africa to the east. Plate separation is accompanied by intrusion of dikes and eruption of lava along the ridge axis. The dikes are fed by magma chamber(s) located beneath the ridge and it has been suggested that the depth of magma chambers is related to the rate of spreading. In order to test this hypothesis we determined the depths of magma chambers beneath the slow spreading Reykjanes Ridge that extends from the Charlie Gibbs fracture zone at 53° north to the southern tip of Iceland at 64° north and the Kolbeinsey Ridge that extends from north of Iceland at about 66 degrees north to the west Jan Mayan ridge at about 71 degrees north in the North Atlantic . Pressures of partial crystallization were calculated from comparison the compositions of natural liquids (glasses) with those of experimental liquids in equilibrium with olivine, plagioclase, and clinopyroxene at different pressures and temperature. Chemical analyses of mid-ocean ridge basalts (MORB) glasses collected along the Reykjanes and Kolbeinsey Ridge were used as liquid compositions. The glasses form by rapid cooling of magma when quenched by contact with seawater, and provide unambiguous samples of natural basalt liquids The calculated pressures were used to estimate the depths of partial crystallization of the host magmas in sub-crustal chambers or reservoirs. The results indicate that the depth of magma chambers of the Reykjanes Ridge decreases from 4 - 8 km (±0.8 km) near the Charlie Gibbs fracture zone to 1.2±0.5 km at 55.67° N. As the Ridge approaches Iceland the depth of chambers increases to 9.7±3 km. The limited data available for the Kolbeinsey Ridge provides only an approximate estimate of the depth of magma chambers (average, 8.2 km) but the depths also seem to increase towards Iceland. The shallow depths obtained for chambers beneath the southern part of the Reykjanes ridge and the average depth of chambers beneath the Kolbeinsey ridge is in contrast with results obtained for slow-spreading ridges elsewhere. This may reflect increased magma flux associated with the Iceland plume, and this is consistent with crustal thickening towards Iceland as suggested by the northerly increase in the maximum depths of chambers along the Reykjanus ridge. The influence of the Iceland plume is apparent from the chemical analyses of the glasses. The abundances of Ti, Na, K, P, and Fe increase whereas the abundances of Si, Mg, Al, and Ca decrease as Iceland is approached. These chemical data can be interpreted in terms of increased magma flux reflecting the thermal effects of the Iceland plume.